2013
DOI: 10.1111/jvs.12109
|View full text |Cite
|
Sign up to set email alerts
|

Landscape‐level variability in historical disturbance in primary Picea abies mountain forests of the Eastern Carpathians, Romania

Abstract: Questions: How have the historical frequency and severity of natural disturbances in primary Picea abies forests varied at the forest stand and landscape level during recent centuries? Is there a relationship between physiographic attributes and historical patterns of disturbance severity in this system? Location: Primary P. abies forests of the Eastern Carpathian Mountains, Romania; a region thought to hold the largest concentration of primary P. abies forests in Europe's temperate zone.Methods: We used dendr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
86
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 105 publications
(94 citation statements)
references
References 65 publications
4
86
1
Order By: Relevance
“…Tree-ring data have been previously used for a variety of research fields ranging from climate reconstructions (Esper et al 2014;Frank et al 2010), forest ecology studies (Esper et al 2007;Svoboda et al 2014), archeological dating (Martin-Benito et al 2014) to reconstructions of geomorphic activity (Gärtner et al 2004;Stoffel and Corona 2014). Tree-rings are a direct measure of radial stem growth, which is closely linked to annual wood formation and carbon accumulation (Bouriaud et al 2005;Kerhoulas and Kane 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Tree-ring data have been previously used for a variety of research fields ranging from climate reconstructions (Esper et al 2014;Frank et al 2010), forest ecology studies (Esper et al 2007;Svoboda et al 2014), archeological dating (Martin-Benito et al 2014) to reconstructions of geomorphic activity (Gärtner et al 2004;Stoffel and Corona 2014). Tree-rings are a direct measure of radial stem growth, which is closely linked to annual wood formation and carbon accumulation (Bouriaud et al 2005;Kerhoulas and Kane 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Primary forests of Norway spruce are very rare in Europe because of a long history of anthropogenic influence. Natural disturbances (e.g., windstorms, bark beetle outbreaks) are the major drivers of primary Norway spruce forest dynamics (Lännenpää et al, 2008;Shorohova et al, 2008;Svoboda et al, 2014;Trotsiuk et al, 2014), and could also influence the climate-growth response of trees (Rozas, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…3a). A previous dendrochronological study by Svoboda et al (2014) revealed a significant effect of topography on the disturbance history of C1. Thus the relatively highly shared effect may also be understood as a topography-induced pattern in the forest stand with a secondary effect on soils (e.g., dbMEM3, Table S.2).…”
Section: High-severity Disturbances and Soil Evolutionmentioning
confidence: 96%
“…A detailed site survey was carried out on sample plots of 500 or 1 000 m 2 (depending on stand density and heterogeneity; Svoboda et al 2014), established using regular randomized selection within an approximately square grid. Orthogonal distances between neighboring plots ranged from 50 to 140 m at C1 and G1, and from 78 to 127 m at S1.…”
Section: Input Datamentioning
confidence: 99%
See 1 more Smart Citation